Unveiling radii and neutron skins of unstable atomic nuclei via nuclear collisions - Tanaka, Masaomi; Horiuchi, Wataru; Fukuda, Mitsunori (Frontiers in Physics, 2024)
Total reaction, interaction, and charge-changing cross sections, which are kinds of cross sections standing for total nuclear collision probability in medium-to high-energy region from a few to several hundred MeV, have been extensively utilized to probe nuclear sizes especially for unstable nuclei. In this mini review, experimental techniques and recent findings from these cross sections are briefly overviewed. Additionally, two new methods to extract neutron skin thickness solely from the above cross sections are explained: One is utilizing the energy and isospin dependence of the total reaction cross sections, and the other is the combination of the total reaction and charge-changing cross section measurements.